Gene Encoding Nitrilase from Soil Sample of Lombok Gold Mine Industry using Metagenomics Approach - Riffiani, Rini; Sulistinah, Nunik; Sunarko, Bambang (KnE Life Sciences, 2017)
This paper describes a efficient screening gene nitrilase from contaminated soil from Lombok gold mine industry. DNA was extracted directly from soil using the soil DNA isolation kit based on enzymatic, chemical and mechanical lysis. The existence of nitrilase gene in soil sample can be identified by nitrilase gene amplification using H1F˗H1R primer. BLASTN analysis result revealed that the nitrilase gene fragment which was amplified by H1F˗H1R primer has a high homology with Rhodococcus rhodochrous strain tg1˗A6 nitrilase gene. These amplification and DNA fragment sequencing results indicated that nitrilase gene existence on soil sample can be identified by metagenomic approach Keywords: Metagenomics; nitrilase gene; Rhodococcus rhodochrous; soil.